Utilization of E-Learning-Based ICT Learning Using the Google Classroom Application During the COVID-19 Pandemic - Ali, Muttaqin Kholis; Maksum, Hasan (LPPM Undiksha, 2020)
The impact of the Covid-19 pandemic has brought changes to the learning process, from face-to-face at school to online distance learning called e-learning. The research objective is to describe the implementation of e-learning-based ICT learning using the Google Classroom application during the Covid-19 pandemic in public high schools. The research used a qualitative approach and was conducted on class X MIA students. 1. Data collection was carried out by observation, interviews, and documentation study. Data analysis was carried out, namely data reduction, data presentation, and concluding. The results showed that the use of the google classroom application made the ICT learning process easier during the covid-19 period. The advantages of the google classroom application as a learning medium are: (1) it has flexibility in terms of time and place; (2) the application is easy to understand and operate; (3) The use of applications is effective and efficient; (4) the learning evaluation process is more accurate. This research concludes that the google classroom application facilitates the ICT learning process during the covid-19 period.